Safe drinking water for small low-income communities: the long road from violation to remediation. (1st April 2022) - Glade, Sara; Ray, Isha
Abstract: Small, low-income communities in the United States disproportionately lack access to safe drinking water (i.e. water that meets regulated quality standards). At a community level, the literature has broadly claimed that a major barrier to safe drinking water access is low technical, managerial, and financial (TMF) capacity. At a broader structural level, the environmental justice literature has shown that historical neglect of low-income communities of color has resulted in numerous water systems without the financial and political resources to meet water quality standards. This study investigates the contemporary processes by which distributive injustices persist in California's Central Valley. The study uses key informant interviews with a range of stakeholders, including employees at the state, county and community, non-profit organizations, and engineers, to understand why sustainable water quality solutions for small low-income communities remain such a challenge. The interviews are structured around a decision chain, which builds out the specific steps needed to go from a maximum contaminant level violation to remediation. The resulting decision chain makes visible the multiple steps at multiple stages with multiple actors that are needed to arrive at a solution to substandard water quality. It shows the numerous nodes at which progress can be stalled, and thus functions as a behind-the-scenes look at the (re)production of persistent inequalities. The complexity of the process shows why having the TMF capacity needed to get to a safe water system is not a reasonable expectation for most small community water systems. Inequalities are continually being produced and cemented, often by the very steps aimed towards remediation, thus making persistent disparities in safe drinking water access a de facto state-sanctioned process that compounds a discriminatory historical legacy.